Bacterionomics and vironomics in carcinogenesis - Pratiwi Sudarmono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
Virus and bacteria are microbes which are very common cause human infection. Most of the bacterial infection can be eradicated by antibiotics and infection symptoms disappear. But for virus infection, once infected, the virus will persistently stay in the host, even undergo not only a lytic cycle but also integrated into host genome. Nowadays, at least 6 virus type are consistently related to human cancer, such as EBV,HPV,HTLV,HBV,HCV,HKSV, and the new one Merkel Virus (MCV). Although not every infected people will get cancer, but around 20% of the whole cancer in human are caused by viral oncogene.Class one oncogenic bacterial is Helicobacter pylori. Infection with this bacteria can cause persistent gastro duodenal inflammation which cause some alteration in gastric cell growth into transformation. Expression of Cag gene and Vac gene and some expression of OMP protein usually link to gastric cancer.Molecular mechanisms of carcinogenesis for every virus which cause infection  is a very complex , which include several processes caused by cell transformation. Besides, other host and environmental factors are also play a significant role in cancer development. Some scientist put a Hallmark analysis as a model to quickly summarize what pathobiology process will happen and what gene or protein caused the process. The Hallmark analysis comprise of several process which may happen simultaneously because some of the Hallmark is caused by the same protein. The Hallmark consists of various virus strategies in oncogenesis such as promoting angiogenesis, avoiding immune destruction, genome instability and mutation, deregulating cellular energetic, resisting cell death, sustaining proliferative signaling, evading growth suppressors, enabling cellular immortality, promoting inflammation and activation metastasis. For example, infection by HPV, will cause low grade dysplasia which can continue to invasive cervical cancer. After host cell transformation, in the long control region genes, E6 and E7 protein will cause several strategies in oncogenesis including resisting cell death and evading growth suppressors.  HBV infection will end without any serious liver damage, but after cell transformation, almost all Hallmark strategies of viral oncogenesis are happening step by step in line with the severity of liver cell damage.As the onset of cancer development after infection can last years, there are an opportunity to design either vaccine or genetic therapy to minimalize further risk of cancer in human